The dynamics of voluntary benchmarking in the water sector - Matias Laine; Eija Vinnari (Routledge, 2025)
This article investigates the dynamics of benchmarking in municipal water
utilities. The authors explain how a voluntary project developed the
characteristics of compulsory benchmarking. While the first adopters of
benchmarking sought efficiency gains, later adoptions have mainly been driven by
institutional pressures. This limits the potential of benchmarking for improving
utility performance.